Challenges of working mothers among female civil servants in Jakarta and Bogor: An existentialism feminist analysis of Simone de Beauvoir - Putri, Fadilla Dwianti; Siscawati, Mia (Harmoni Sosial: Jurnal Pendidikan IPS, 2023)
This research explores the experiences of female civil servants in Jakarta and Bogor regarding the social constructions that shape their roles as wives and mothers. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews and observations during October-November 2022 using Simone de Beauvoir's feminist existentialism framework. This study found that female civil servants are still expected to bear the full burden of domestic work despite their role in the public sphere. As a result, women often experience a double burden and are hindered from getting promoted. This is due to the view that women's role in the public sphere is secondary, in line with the legacy of the "ibuism" ideology introduced during the new order era. This reinforces the precedent that women's primary career is in the domestic sphere. Based on these findings, a more equitable division of labor and support systems for female civil servants in the domestic sphere and the workplace are needed. Thus, female civil servants can optimally perform their duties and have the opportunity to be promoted equally with male civil servants. By demonstrating the gap between society's expectations and the professional realities experienced by these women, this research contributes to the broader discourse on gender equality in the bureaucratic system. This research can serve as a basis for developing policies and mechanisms to foster a more supportive environment for female civil servants.